Combatiendo la alienación del empleado en el trabajo: Qué papel puede jugar la justicia organizativa? - Pablo Zoghbi Manrique de Lara; Guillermo Caama\~no Brito (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2011)
The present study examines the impact of organizational justice on the three dimensions of work alienation identified by Seeman (1959), i.e., powerlessness, meaninglessness and selfestrangement. It is argued that the three common types of organizational justice (i.e., procedural, distributive, and interactional) could lead employees to perceive their organization as illegitimate and lacking values and, hence, to feel detached and alienated from it. Structural equation modeling (SEM) results found a significant negative relationship between organizational justice and work alienation in the case of distributive justice and, in particular, for the powerlessness and meaninglessness dimensions of work alienation. The findings suggest that policies for the monitoring of distributive justice perceptions by the employees may be effective in combating work alienation and, hence, its harmful recognized effects in the workplace. The article also offers implications, limitations and avenues for future research.
Keywords: M12; M54; 330; organizational justice; work alienation